Women’s empowerment within the development paradigm: a discourse analysis of selected government and non- governmental women’s empowerment frameworks - Mzima, Mihlali (My University, 2020)
The expansion of the conceptualisation of empowerment to include gender discourses into the contemporary development agenda triggered the emergence of women’s empowerment as a transformative movement aimed at deconstructing the myth of neutrality in policies and replacing this with a more engaged acknowledgement of gender power relations. Borne from this was the integration of the socio-political objectives of women’s empowerment discourse into other developmental arenas, including education, employment, property rights, reproductive and sexual rights, income equality, access to resources and the distribution of work. Drawing from the works of contemporary development theorists, such as Naila Kabeer and Srilatha Batliwala, this research employs a critical discourse analysis methodological approach to debunk the ideological frameworks and objectives of the selected South African government policy (the National Framework for Women’s Empowerment and Gender Equality) and non-governmental strategies (from 18Twenty8 – a women led NGO) dedicated to women’s empowerment. The aim here is not to scrutinise the implementation of the policies and programmes of the chosen case studies or how these institutions operate, the aim is rather to analyse how the language used in the chosen documents informs how we understand women’s empowerment within the development paradigm. The key findings of the research reiterate the arguments made in the literature review and confirm the expected outcomes which indicate that women’s empowerment shifted from being a social-political transformation motivated concept to being a ‘buzzword’ to make neoliberal interests more palatable in the contemporary (neoliberal) development era. Thus, it is concluded that the conceptualisations of women’s empowerment in the selected policies and programmes do not offer transformative discourses that can be used to dismantle and rebuild institutional structures, challenge the existing gender power relations and absolve discriminative stereotypes and norms that contribute to the disempowerment of women. Instead, these documents offer women’s empowerment discourses that are underpinned by mainstream anti-poverty and basic needs approaches to development disguised as women’s empowerment discourses and ignoring the most important objective of the concept of ‘empowerment’ - which is to embed power within any and every activity and discourse advocating for social change and progress
A research report submitted in partial fulfilment of the requirements of the degree of MA (Development Studies) in the Faculty of Humanities, University of the Witwatersrand, 2020